(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The aim of this paper, which uses data from the Public Violence Yearbook 2022 to value the pedagogical theater as a war machine in fighting violence against children, is to understand the potential in watching and acting on theatrical activities performed in schools. It argues that supressing the themes encompassing gender and sexualities from the official curriculum, as well as the social isolation of students in their households after the Covid-19 pandemics, have made it difficult for children and young people to access support networks and safe spaces to report and fight the abuses suffered.